Exploring hope : case studies of innovation, change and development in the global south - Sili, Marcelo; Kozel, Andrés; Mizbar, Samira; Sharma, Aviram; Casado. Ana (Diverse perspectives on creating a fairer society, 2024)
The future in the Global South is viewed and perceived critically, from the inertia of a present that does not offer peace, justice, wealth and happiness, but from a view constructed from poverty, marginality, war and chaos. Exploring Hope seeks to qualify, question and even refute the monolithic ideas and images of the impossibility of building opportunities for improving the quality of life and overcome the different constraints of development in the Global South. With contributions from Argentina, Colombia, Chile, Bolivia, Paraguay, Brazil, Ecuador, Venezuela, Mexico, Cameroon, Ghana, Morocco, Congo, Kenya, Senegal, South Africa, China, Pakistan, India, Indonesia, Sri Lanka, Bangladesh, Afghanistan and Bhutan, authors identify innovative, successful projects and processes that are structurally impacting models of development, and that make it possible to imagine new developmental paths in the Global South. Split into five sections covering economic, demographic, political, social, cultural and environmental issues, each chapter presents cases where emerging initiatives are integrated into the current socio-technical regime and contextualised within regional needs. Focusing on hope rather than challenges, this edited collection presents a powerful evocation of ongoing opportunities for building a better future in the Global South and beyond.